KARAKTERISTIK KOMUNIKASI NABI MUHAMMAD SAW. (ANALISIS TERHADAP HADIS METODE DAKWAH) - Arief Wangsa, Fadhlina; Perdana Rayyn, I Gusti Bagus Agung; Mahar, Al-Fiana (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2022)
This article discusses the characteristics of the communication of the Prophet Muhammad, in preaching. In this article, there are several important things that will become the core of the discussion, namely, the definition of da'wah, methods or procedures for preaching the Prophet Muhammad. as well as the communicative characteristics of the Prophet Muhammad, to the target of his da'wah. Therefore, it is necessary to explain these things so as not to cause mistakes and misunderstandings in preaching. The study of this problem was carried out by conducting a literature review with a linguistic approach to the hadith of the Prophet Muhammad. So the conclusion is that da'wah is an activity to convey news, while the da'wah method is the method used by news bearers. As for the method and characteristics of the Prophet Muhammad's da'wah. that is, by conveying good news, not making it difficult, conveying it politely and full of wisdom.